Public participation in decision-making on the coverage of new antivirals for hepatitis C. Issue 5 (15th August 2016) - Kieslich, Katharina; Ahn, Jeonghoon; Badano, Gabriele; Chalkidou, Kalipso; Cubillos, Leonardo; Hauegen, Renata Curi; Henshall, Chris; Krubiner, Carleigh B; Littlejohns, Peter; Lu, Lanting; Pearson, Steven D; Rid, Annette; et al.
Abstract : Purpose: New hepatitis C medicines such as sofosbuvir underline the need to balance considerations of innovation, clinical evidence, budget impact and equity in health priority-setting. This article examines the role of public participation in addressing these considerations. Design/methodology/approach: The article employs a comparative case study approach. It explores the experience of four countries–Brazil, England, South Korea and the USA–in making coverage decisions about the antiviral sofosbuvir and involving the public and patients in these decision-making processes. Findings: Issues emerging from public participation activities include the role of the universal right to health in Brazil, the balance between innovation and budget impact in England, the effect of unethical medical practices on public perception in South Korea, and the legitimacy of priority-setting processes in the USA. Providing policymakers are receptive to these issues, public participation activities may be re-conceptualized as processes that illuminate policy problems relevant to a particular context, thereby promoting an agenda-setting role for the public. Originality/value: The article offers an empirical analysis of public involvement in the case of sofosbuvir, where the relevant considerations that bear on priority-setting decisions have been particularly stark. The perspectives that emerge suggest that public participation contributes to raising attention to issues that need to be addressed by policymakers. Public participation activities can thus contribute to setting policy agendas, even if that is not their explicit purpose. However, the actualization of this contribution is contingent on the receptiveness of policymakers.